Construction of Women in Reporting Cases of Sexual Violence in Online Mass Media - Yulfiha, Yulfiha Nur Azizah; Muhammad Badrus Siroj (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
This research aims to determine the construction of women in the reporting of sexual violence in the media Kompas.com and Detik.com. The dismantling of the construction of women as victims is carried out by analyzing news discourse using Norman Fairclough’s critical discourse analysis theory. The data collection method and technique used is the listening method with basic tapping techniques. The data analysis method and technique uses the matching method and the distribution method. The matching method uses the basic technique of Sorting Determining Elements (PUP) with the advanced techniques of Connecting Appeals to Equalize (HBS) and Connecting Appeals to Differentiate (HBB). In addition, data analysis is also supported by the application of Norman Fairclough’s Critical Discourse Analysis approach, including the stages of description, interpretation, and explanation. Through the data analysis, it is known that both media construct women as victims, weak, powerless, vulnerable to deception, trapped in power relations, but brave to fight back at the same time. Both media also have a tendency to protect the perpetrator by giving the initials of the name, not only the victim who is protected. In terms of text consumption, it shows that most readers condemned the perpetrator’s actions, but one Kompas.com reader sexually objectified the victim’s body. From a sociocultural perspective, several phenomena are related to the media’s construction of women in cases of sexual violence. These phenomena include revenge porn, marital rape, unequal power relations, the practice of marrying rape victims to their perpetrators, and beauty privilege for women. Key Words: critical discourse analysis, Norman Fairclough, women, sexual violence, Kompas.com, Detik.com